Proinflammatory Soluble Interleukin-15 Receptor Alpha Is Increased in Rheumatoid Arthritis. (25th July 2012) - Machado Diaz, Ana Cecilia; Chico Capote, Araceli; Arrieta Aguero, Celia Aurora; Rodríguez Alvarez, Yunier; García del Barco Herrera, Diana; Estévez del Toro, Miguel; Guillen Nieto, Gerardo E.; Santos Savio, Alicia
Abstract : Rheumatoid arthritis (RA) is an autoimmune and inflammatory disease in which many cytokines have been implicated. In particular, IL-15 is a cytokine involved in the inflammatory processes and bone loss. The aim of this study was to investigate the existence in synovial fluid of soluble IL-15R α, a private receptor subunit for IL-15 which may act as an enhancer of IL-15-induced proinflammatory cytokines. Soluble IL-15R α was quantified by a newly developed enzyme-linked immunosorbent assay (ELISA) in samples of synovial fluid from patients with RA and osteoarthritis (OA). The levels of IL-15R α were significantly increased in RA patients compared to OA patients. Also, we studied the presence of membrane-bound IL-15 in cells from synovial fluids, another element necessary to induce pro-inflammatory cytokines through reverse signaling. Interestingly, we found high levels of IL-6 related to high levels of IL-15R α in RA but not in OA. Thus, our results evidenced presence of IL-15R α in synovial fluids and suggested that its pro-inflammatory effect could be related to induction of IL-6.